Laser Ablation Synthesis and Characterization of Gold-Zirconium Oxide Nanoparticles - Ali Fadhil Abdulaali (Jurnal MIPA dan Pembelajarannya, 2026)
The synthesis and characterization of gold-zirconium oxide (Au-ZrO₂) nanoparticles by Pulsed Laser Ablation in Liquid (PLAL) technique is presented. The stable colloidal suspensions of gold and zirconium nanoparticles were generated by ablation of targets made of high purity gold and zirconium, respectively, in deionized water at different laser energies. The obtained nanomaterials were deposited onto the substrates by drop-casting and then subjected to calcination to improve the crystallinity and bonding at the interface. UV–Vis spectroscopy was utilized to investigate the optical properties, which showed prominent surface plasmon resonance (SPR) peaks for Au nanoparticles and broad absorbance range characteristic of the ZrO₂ wide band gap. The crystallite size of the Au and ZrO₂ phases was determined to be ~ 14.2–14.4 nm, respectively, by X-ray diffraction (XRD) analysis, and the phases formed were found to be face-centered cubic (FCC) Au and cubic ZrO₂. The images obtained by Field Emission Scanning Electron Microscopy (FESEM) showed uniformity in morphology, the nanometric particle size and possibility of core–shell structures. Overall, the Au-ZrO₂ nanocomposites synthesized by PLAL demonstrate structural and optical properties suitable for various applications, including gas sensing, photocatalysis, and optoelectronics, highlighting the potential of PLAL for producing high-performance advanced nanomaterials.